ANALISIS IMPLEMENTASI PEMBIAYAAN MURABAHAH DAN PENGARUHNYA TERHADAP KESEJAHTERAAN EKONOMI NASABAH: STUDI PADA BPRS BUMI RINJANI KEPANJEN KANTOR KAS DONOMULYO - Ferlina, Dian; Moh. Aan Sulton (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Financing refers to the disbursement of funds by banks to customers. In Islamic banking, financing takes various forms depending on the contract (akad), one of which is murabahah financing. This study examines the process of murabahah financing, from application and analysis to realization, at BPRS Bumi Rinjani Kepanjen, Donomulyo Branch. The findings indicate that the implementation of murabahah financing in accordance with Sharia principles provides significant benefits to customers, including increased income and business growth. The primary contribution of this financing product is its ability to enhance customers' economic well-being through flexible and Sharia-compliant access to capital. These findings affirm that murabahah financing at BPRS holds great potential as an effective Sharia-based economic empowerment tool for improving the welfare of the Donomulyo village community.